2011
DOI: 10.1111/j.1447-0349.2011.00758.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the acceptability of door locking to staff, patients, and visitors on acute psychiatric wards

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(76 citation statements)
references
References 12 publications
1
72
1
2
Order By: Relevance
“…Patients have been shown to experience feelings of distress such as aggression, anger, irritation, depression and low self-esteem during treatment on a locked acute psychiatric ward [12,13]. Haglund and von Essen [14] showed that locked doors may evoke feelings of confinement, forced dependence on staff or negative emotions in voluntarily admitted inpatients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients have been shown to experience feelings of distress such as aggression, anger, irritation, depression and low self-esteem during treatment on a locked acute psychiatric ward [12,13]. Haglund and von Essen [14] showed that locked doors may evoke feelings of confinement, forced dependence on staff or negative emotions in voluntarily admitted inpatients.…”
Section: Introductionmentioning
confidence: 99%
“…A German study found that admission to an open ward was associated with a more positive experience than admission to a locked ward [17]. Furthermore, opening and locking doors may increase the workload for nurses and reduce time for engagement in therapeutic activities with patients [13,14,18]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…61 A survey of patient, staff and visitor perceptions found that whilst there was general agreement that locking doors appeared to reduce absconding, staff expressed feelings of guilt, embarrassment and fear of being blamed when a patient absconded. 62 Staff also reported that open wards created anxious vigilance to prevent absconding and increased the workload in allocating staff to watch the door, whereas staff on partially-locked doors also perceived an increased workload in letting people in and out of the ward. Patients had mixed feelings about the status of the door and expressed depression, a sense of stigma and low self-esteem when the door was locked.…”
Section: Absconding and Locked Mental Health Unitsmentioning
confidence: 96%
“…In particular, ratings of self-esteem, self-efficacy and optimism and control over the future were higher among inpatients than among service users in the community. This finding initially appears counterintuitive, given that the doors of inpatient units are often locked, reportedly creating feelings of depression and low self-esteem, 153 and that service users are more likely to face a range of restrictions. 154 However, on reflection and in the light of some of the qualitative data in which service users outline how the period in hospital had been a necessary and important stage in their recovery, perhaps this is more understandable.…”
Section: Making Connections In Inpatient Mental Health Care Planning mentioning
confidence: 99%